Long-term triple therapy de-escalation to indacaterol/glycopyrronium in COPD patients (SUNSET): a randomized, double-blind, triple-dummy clinical trial - Chapman,KR; Hurst,JR; Frent,S; Larbig,M; Fogel,R; Guerin,T; Banerji,D; Patalano,F; Goyal,P; Pfister,P; Kostikas,K; Wedzicha,JA (American Journal of Respiratory and Critical Care Medicine, 2018)
Rationale: There are no studies on ICS withdrawal in patients on long-term triple therapy in the absence of frequent exacerbations. Objective: To evaluate the efficacy and safety of the direct de-escalation from long-term triple therapy to indacaterol/glycopyrronium in non-frequently exacerbating COPD patients. Methods: This 26-week, randomized, double-blind, triple-dummy study assessed the direct change from long-term triple therapy to indacaterol/glycopyrronium (110/50μg once daily) or continuation of triple therapy (tiotropium 18μg once daily plus combination of salmeterol/fluticasone propionate [50/500μg] twice daily) in non-frequently exacerbating patients with moderate-to-severe COPD. Primary endpoint was non-inferiority on change from baseline in trough forced expiratory volume in 1 second (FEV1). Moderate or severe exacerbations were predefined secondary endpoints. Measurements and Main Results: 527 patients were randomized to indacaterol/glycopyrronium and 526 to triple therapy. ICS withdrawal led to a reduction in trough FEV1 of −26mL (95% confidence interval [CI], −53 to 1 mL) with confidence limits exceeding the non-inferiority margin of −50 mL. The annualized rate of moderate or severe COPD exacerbations did not differ between treatments (rate ratio 1.08; 95%CI, 0.83 to 1.40). Patients with ≥300 blood eosinophils/μL at baseline presented greater lung function loss and higher exacerbation risk. Adverse events were similar in the two groups. Conclusions: In COPD patients without frequent exacerbations on long-term triple therapy, the direct de-escalation to indacaterol/glycopyrronium led to a small decrease in lung function, with no difference in exacerbations. The higher exacerbation risk in patients with ≥300 blood eosinophils/µL suggests that these patients are likely to benefit from triple therapy. Clinical trial registration available at www.clinicaltrials.gov, ID NCT02603393.